Biomechanical analysis of lumbar interbody fusion cages with various lordotic angles: a finite element study. Issue 3 (17th February 2018) - Zhang, Zhenjun; Fogel, Guy R.; Liao, Zhenhua; Sun, Yitao; Liu, Weiqiang
Abstract: Inappropriate lordotic angle of lumbar fusion cage could be associated with cage damage or subsidence. The biomechanical influence of cage lordotic angle on lumbar spine has not been fully investigated. Four surgical finite element models were constructed by inserting cages with various lordotic angles at L3-L4 disc space. The four motion modes were simulated. The range of motion (ROM) decreased with increased lordotic angle of cage in flexion, extension, and rotation, whereas it was not substantially changed in bending. The maximum stress in cage decreased with increased lordotic angle of cage in all motion modes. The maximum stress in endplate at surgical level increased with increased lordotic angle of cage in flexion and rotation, whereas it was not substantially changed in extension and bending. The facet joint force (FJF) was much smaller than that for the intact conditions in extension, bending, and rotation, while it was not substantially changed in flexion. In conclusion, the ROM, stresses in the cage and endplate at surgical level are sensitive to the lordotic angle of cage. The increased cage lordotic angle may provide better stability and reduce the risk of cage damage, whereas it may increase the risk of subsidence in flexion and rotation.